2017
DOI: 10.5194/isprs-archives-xlii-1-w1-305-2017
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of Mikania Micrantha on Land Cover and Maxent Modeling to Predict Its Potential Invasion Sites

Abstract: ABSTRACT:Mikania micrantha is one of the major invasive alien plant species in tropical moist forest regions of Asia including Nepal. Recently, this weed is spreading at an alarming rate in Chitwan National Park (CNP) and threatening biodiversity. This paper aims to assess the impacts of Mikania micrantha on different land cover and to predict potential invasion sites in CNP using Maxent model. Primary data for this were presence point coordinates and perceived Mikania micrantha cover collected through systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Similarly, in Nepal, several studies have been carried out regarding species habitat suitability using MaxEnt (Bai et al, 2018). The habitat suitability for mammals, birds, vegetation, and even invasive plant species habitat analysis was previously conducted (Khadka & Pandey, 2014;Baidar et al, 2017;Linshan et al, 2017;Acharya et al, 2018;Bista et al, 2018;Chhetri et al, 2018;Lamsal et al, 2018;Rana et al, 2018;Thapa et al, 2018). More specifically, Kafley et al (2009) used data for MaxEnt modelling of species geographic distributions for predicting the probability of occurrence of rhinos in Chitwan National Park and found that the national park can sustain more individuals (then time individuals; 512).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Nepal, several studies have been carried out regarding species habitat suitability using MaxEnt (Bai et al, 2018). The habitat suitability for mammals, birds, vegetation, and even invasive plant species habitat analysis was previously conducted (Khadka & Pandey, 2014;Baidar et al, 2017;Linshan et al, 2017;Acharya et al, 2018;Bista et al, 2018;Chhetri et al, 2018;Lamsal et al, 2018;Rana et al, 2018;Thapa et al, 2018). More specifically, Kafley et al (2009) used data for MaxEnt modelling of species geographic distributions for predicting the probability of occurrence of rhinos in Chitwan National Park and found that the national park can sustain more individuals (then time individuals; 512).…”
Section: Introductionmentioning
confidence: 99%